Profiling of cytokines in human epithelial ovarian cancer ascites - Matte, Isabelle (e-Century Publishing Corporation, 2012)
BACKGROUND: The behavior of tumor cells is influenced by the composition of the surrounding tumor environment. The importance of ascites in ovarian cancer (OC) progression is being increasingly recognized. The characterization of soluble factors in ascites is essential to understand how this environment affects OC progression. The development of cytokine arrays now allows simultaneous measurement of multiple cytokines per ascites using a single array. METHODS: We applied a multiplex cytokine array technology that simultaneously measures the level of 120 cytokines in ascites from 10 OC patients. The ascites concentration of a subset (n = 5) of cytokines that was elevated based on the multiplex array was validated by commercially available ELISA. The ascites level of these 5 cytokines was further evaluated by ELISA in a cohort of 38 patients. Kaplan-Meier analysis was used to assess the association of cytokine expression with progression-free survival (PFS) in this cohort. RESULTS: We observed a wide variability of expression between different cytokines and levels of specific cytokines also varied in the 10 malignant ascites tested. Fifty-three (44%) cytokines were not detected in any of the 10 ascites. The level of several factors including, among others, angiogenin, angiopoietin-2, GRO, ICAM-1, IL-6, IL-6R, IL-8, IL-10, leptin, MCP-1, MIF NAP-2, osteprotegerin (OPG), RANTES, TIMP-2 and UPAR were elevated in most malignant ascites. Higher levels of OPG, IL-10 and leptin in OC ascites were associated with shorter PFS. IL-10 was shown to promote the anti-apoptotic activity of malignant ascites whereas OPG did not. CONCLUSION: Our data demonstrated that there is a complex network of cytokine expression in OC ascites. Characterization of cytokine profiles in malignant ascites may provide information from which to prioritize key functional cytokines and understand the mechanism by which they alter tumor cells behavior. A better understanding of the cytokine network is essential to determine the role of ascites in OC progression.